A Maternal Two-meal Feeding Sequence with Varying Crude Protein Affects Milk Lipid Profile in A Sow-Piglet Model. Issue 1 (December 2017) - Wu, Xin; Xie, Chunyan; Guo, Xiaoyun; Long, Cimin; Zhang, Tianyong; Gao, Tianzeng; Yin, Yulong
Abstract The effects of a two-meal feeding sequence on production performance and milk lipid profile were investigated. Sixty pregnant sows (d 85 of gestation) were assigned to 3 groups: 2 C group (fed a control crude protein [CP] diet at 0600 and 1500 daily), LH group (fed a low CP diet and a high CP diet at 0600 and 1500), or HL group (fed a high CP diet and a low CP diet at 0600 and 1500). Reproductive performance of sows, and lipid profiles of plasma and milk were measured. Results showed that the HL feeding sequence dramatically increased average piglet weight/litter, average daily gain of piglet/litter, and milk production of sows. LH feeding sequence increased milk fat proportion, and HL feeding sequence significantly increased the proportion of milk MUFA on d 14 and 21 of lactation. Interestingly, the HL feeding sequence also reduced the ratio of C18:1cis /C18:1trans in milk, which may account for the greater milk production of sows and growth performance of piglets during lactation. These findings indicated that both the maternal two-meal feeding sequences with varying crude protein improved milk production and milk lipid profiles of sows, which might contribute to improving growth performance of piglets.